Passionate love and popular cinema : romance and film genre - Todd, Erica (Palgrave Macmillan, 2014)
This book analyses the romantic drama and the way that passionate love is presented as the central storyline in popular cinema, drawing upon genre studies and sociology. Exploring the passionate love story as a cinematic form, it also contributes, through comparison, to research on the romantic comedy.